Entrepreneurship Workshop in Kampung Nelayan’s Community, Medan Belawan District - Hanny Siagian; William William; Nasrul Efendi Fendi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Approximately 600 families inhabit the Kampung Nelayan of Medan Belawan District; most of them work as fishermen. The people of Kampung Nelayan have limited facilities and relatively low knowledge of entrepreneurship which caused an inability to maximize the potential of marine natural resources and mangrove forest resources. Entrepreneurship workshop activities are carried out to equip the public to have a good knowledge of entrepreneurship, which is expected to generate and increase the spirit of entrepreneurship in utilizing and managing the potential of natural resources into high selling value products. The activities were carried out using a quasi-experimental one-group pretest-posttest approach. The results of the pretest and post-test were used to measure changes in participants knowledge. The results of the outreach activities showed that there was a change in participants entrepreneurial knowledge, marked by an increase in the average number of pretest and post-test scores. However, in terms of the number of individual scores, there were variations in participants' knowledge, namely increasing, constant, and decreasing. Following up on this result, it is necessary to conduct entrepreneurship assistance and workshops to implement knowledge in managing businesses and marketing them to improve the economy.